COMMUNICATION NETWORK RELIABILITY AND AVAILABILITY ESTIMATION BY THE SIMULATION METHOD - Slavko Pokorni J. (Vojnotehnicki glasnik/Military Technical Courier, 2011)
The paper gives an estimation of two-terminal availability for a co-mplex communication network (up to 50 nodes and 150 links) by a softw- are package developed by the authors and based on the Monte Carlo s- imulation method and Weibull distribution. Reliability can be estimated as well. The software package is written in VISUAL BASIC 6.0 programing la- nguage on an MSI laptop with the Windows XP Professional operating system. The program execution time with over 500000 iterations is a few seconds (without graphical display). The Weibull distribution function, used for availability estimation, can be applied for electronic, electromech- anical and mechanical components as well as with different failure rates.